2008
DOI: 10.1080/10641950701885170
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Circulating Trophoblast Particles in Peripheral Maternal Blood in Preeclampsia Complicated Pregnancies

Abstract: The number of trophoblast particles in peripheral maternal blood of preeclamptic pregnancies was significantly higher than in non-preeclamptic pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 26 publications
2
15
0
2
Order By: Relevance
“…The mean length of SNAs was 72 ± 21 μm (range 42-116), which is comparable to the size of SNAs reported in various vascular beds in vivo (decidual vein 50 μm [16] , broad ligament vein 40-75 μm [17] , uterine vein 10-200 μm [20,24,35] , lungs 12-150 μm [22,[36][37][38] and peripheral circula- [16,17,[24][25][26][27][28] ). In addition, we observed 3 general morphologies/shapes for our SNAs; teardrop, rounded and irregular, which are also the same as those reported for SNAs in vivo [24] .…”
Section: Dna Content and Metabolic Activity Of Snassupporting
confidence: 71%
See 1 more Smart Citation
“…The mean length of SNAs was 72 ± 21 μm (range 42-116), which is comparable to the size of SNAs reported in various vascular beds in vivo (decidual vein 50 μm [16] , broad ligament vein 40-75 μm [17] , uterine vein 10-200 μm [20,24,35] , lungs 12-150 μm [22,[36][37][38] and peripheral circula- [16,17,[24][25][26][27][28] ). In addition, we observed 3 general morphologies/shapes for our SNAs; teardrop, rounded and irregular, which are also the same as those reported for SNAs in vivo [24] .…”
Section: Dna Content and Metabolic Activity Of Snassupporting
confidence: 71%
“…Despite this challenge, several groups have reported successful isolation of SNAs from maternal peripheral blood [16,17,[24][25][26][27][28] as early as at 6 weeks of gestation [25] . Since SNAs may contain predominantly fragmented DNA, the quality and utility of the DNA may not be adequate for use in diagnostics, but this has not been tested.…”
mentioning
confidence: 99%
“…They showed that after the 30th gestational week, OPN is only present in cytotrophoblasts of preeclamptic placentas, but not in healthy ones (53). It was previously reported that a significantly higher amount of trophoblast debris can be found in the maternal circulation in preeclampsia compared to women with a normal pregnancy (41,42,54). Based on these observations, we examined the association between the concentrations of circulating fetal DNA as a marker of trophoblast debris, and OPN in maternal blood.…”
Section: Discussionmentioning
confidence: 96%
“…We recently demonstrated that the number of trophoblast cells in maternal blood of preeclamptic pregnancies was significantly higher than in non-preeclamptic pregnancies. Whereas the fetal origin of the detected cells were verified by XY-FISH analysis in women delivering a boy, for women delivering a girl, no additional characterization was possible [18] .…”
Section: Discussionmentioning
confidence: 98%
“…The fetal origins of the detected cells were verified by XY-FISH analysis in women delivering a boy. Unfortunately, for women delivering a girl, no additional characterization was possible [18] .…”
Section: Introductionmentioning
confidence: 99%